Practical guide to surgical and endovascular hemodialysis access management : Case based illustration - Cho, Kyung J; Ko, Po-Jen; Chu, Sung-Yu; Gopinathan, Anil; Ho, Jackie Pei (World Scientific Publishing Company, 2016)
This book serves as a practical guide for clinicians and nurses involved in creating and managing hemodialysis access for renal failure patients. It covers fundamental principles, management of common and complex cases, and includes illustrative clinical examples.